MoS2 Functionalized Multicore Fiber Probes for Selective Detection of Shigella Bacteria Based on Localized Plasmon - Kumar, Santosh; Guo, Zhu; Singh, Ragini; Wang, Qinglin; Zhang, Bingyuan; Cheng, Shuang; Liu, Feng-Zhen; Marques, Carlos; Kaushik, Brajesh Kumar; Jha, Rajan (Journal of lightwave technology, 2021)
Present study demonstrates the fiber-optic localized surface plasmon resonance (LSPR) based sensitive biosensor for detection of Shigella bacterial species. The proposed sensor is comprised of multi-core fiber (MCF) having seven cores arranged in a hexagonal shape and spliced with single-mode fiber (SMF) for efficient detection. An increase in evanescent waves (EWs) and coupling of modes between MCF cores was achieved by etching process in a controlled manner. The etching process also increases the refractive index sensitivity (RIS) of the proposed sensor. Further, coating with nanomaterials like gold nanoparticles (AuNPs) and molybdenum disulfide (MoS 2 ) helps in the excitation of localized plasmons. Here, Shigella specific oligonucleotide probes are used as a recognition element. The results demonstrate that the proposed sensor can successfully and efficiently detect the Shigella bacterial species with high sensitivity. Shigella in the range of 10 - 100 CFU/mL (colony-forming unit/mL) can cause serious intestinal infection and therefore, its detection in this range is critical. The proposed sensor demonstrates a linearity range from 1 to 10 9  CFU/mL with a detection time of 5 min and a limit of detection (LoD) of 1.56 CFU/mL. The proposed sensing methodology can be a potential alternative to the commercially existing ones in the near future.